The Substitution of Noodles Made from Banana Flour and Cassava Leaf Flour as Functional Food: Subtitusi Mie Berbahan Tepung Pisang dan Tepung Daung Singkong Sebagai Pangan Fungsional - Aprianti, Dwi; Rosita, Rifka; Rantani, Dea; Rate, Suherman (Jurnal Kesehatan Ilmiah Aufa Royhan, 2023)
Noodles are a processed food rich in starch made from flour moulded lengthwise like threads and are one of the favourite foods of Indonesian people. This activity aims to find out the noodle formulation by substituting banana flour and cassava leaf flour and the results of organoleptic tests and proximate analysis. The research method was carried out experimentally using a Completely Randomized Design (RAL). The Kruskall Wallis test results, colour, aroma, texture and taste parameters showed P<0.05, there was a significant difference in the treatment of F1, F2, F3, and F4 with the substitution of banana flour and cassava leaf flour. The ANOVA test results showed P<0.05, there were significant differences in the F1, F2, F3, and F4 treatments on water content, ash content, protein content, fat content, crude fibre content and carbohydrate content in noodles with the substitution of banana flour and leaf flour. cassava. This activity concludes that there is a real difference in the treatment of F1, F2, F3, and F4 with the substitution of banana flour and cassava leaf flour. There were real differences in the treatment of F1, F2, F3, and F4 on water content, ash content, protein content, fat content, crude fibre content and carbohydrate content in noodles with the substitution of banana flour and cassava leaf flour. The suggestion from this research is that banana flour and cassava leaf flour have the potential to substitute ingredients for wheat in making functional foods.